The Impact of Components in Marketing - Mix Strategy on Customer Satisfaction and Loyalty: Case Study at Codegym Vietnam Joint Stock Company, Hue Branch - Chien, Nguyen Dinh; Minh, Dao Duy; Vui, Mai Thi (International Review of Management and Marketing, 2024)
This study aims to analyze the impact of 7 components on the marketing - mix strategy on the satisfaction and loyalty of programming course students at the branch of CodeGym Vietnam Joint Stock Company in Hue. The study combined exploratory factor analysis (EFA), and confirmatory factor analysis (CFA) to measure the impacts of each component into the success of marketing - mix strategy then applied linear structural modeling (SEM) to test the related hypothesis of driving parameters to the customers’ satisfaction and loyalty. The finding indicated that there are 3 major factors having positively impact on customer satisfaction and loyalty, including: product, distribution and process. On the contrary, price, promotion, people and facilities factors have a negative impact on student satisfaction. The study also suggests several important implications to enhancing the efficiency of marketing mix strategy - with a need to focusing on developing marketing mix programs for centers to enhance customer satisfaction and loyalty.